Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/jgs.12942
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and Potentially Inappropriate Medication Use in Older Adults with Cancer Undergoing Chemotherapy: Effect on Chemotherapy‐Related Toxicity and Hospitalization During Treatment

Abstract: Polypharmacy and potentially inappropriate medication (PIM) use are understudied among older adults with cancer undergoing chemotherapy. The current study’s aims were to evaluate in this population: 1) the prevalence of polypharmacy and PIM use; and 2) the association between these and chemotherapy-related adverse events. Methods This was a secondary analysis of prospectively collected data of adults age ≥65 years with cancer undergoing chemotherapy. Measures included: the number of daily medications (i.e, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 35 publications
(68 reference statements)
6
101
4
3
Order By: Relevance
“…Previous studies had identified anticoagulants and oral hypoglycemics such as metformin/ glyburide to be 'high risk' medication classes for adverse drug events in the elderly population based on the Beers, Zhang, and Drugs to Avoid in the Elderly criteria [21,22]. However, their results suggested no association between polypharmacy and potentially inappropriate medication use with chemotherapyrelated toxicity or hospitalization in seniors with cancer [21].…”
Section: Results Interpretationmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous studies had identified anticoagulants and oral hypoglycemics such as metformin/ glyburide to be 'high risk' medication classes for adverse drug events in the elderly population based on the Beers, Zhang, and Drugs to Avoid in the Elderly criteria [21,22]. However, their results suggested no association between polypharmacy and potentially inappropriate medication use with chemotherapyrelated toxicity or hospitalization in seniors with cancer [21].…”
Section: Results Interpretationmentioning
confidence: 57%
“…In addition to the quantity of medications, types of medications were also important in evaluating potential adverse drug interaction with chemotherapy [21,22]. Previous studies had identified anticoagulants and oral hypoglycemics such as metformin/ glyburide to be 'high risk' medication classes for adverse drug events in the elderly population based on the Beers, Zhang, and Drugs to Avoid in the Elderly criteria [21,22].…”
Section: Results Interpretationmentioning
confidence: 99%
“…The MAI has primarily been studied in older veterans; currently no comprehensive study has used MAI for patients with cancer [13][14][15][16][17]. Despite the lack of data, the MAI could be used and modified for the cancer patient because the 10-item list evaluates relevant aspects of care for a patient with cancer.…”
Section: Patients With Cancermentioning
confidence: 99%
“…STOPP incorporates 65 criteria that are also organized by physiologic system, with additional focus on analgesics, duplicate drug classes, and drugs that increase fall risk. These screening tools were developed by a consensus panel of 18 experts [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Start/stoppmentioning
confidence: 99%
See 1 more Smart Citation